Cybersecurity Threats with New Perspectives - Sarfraz, Muhammad (IntechOpen, 2021)
Cybersecurity is an active and important area of study, practice, and research today. It spans various fields including cyber terrorism, cyber warfare, electronic civil disobedience, governance and security, hacking and hacktivism, information management and security, internet and controls, law enforcement, national security, privacy, protection of society and the rights of the individual, social engineering, terrorism, and more. This book compiles original and innovative findings on issues relating to cybersecurity and threats. This comprehensive reference explores the developments, methods, approaches, and surveys of cyber threats and security in a wide variety of fields and endeavors. It specifically focuses on cyber threats, cyberattacks, cyber techniques, artificial intelligence, cyber threat actors, and other related cyber issues. The book provides researchers, practitioners, academicians, military professionals, government officials, and other industry professionals with an in-depth discussion of the state-of-the-art advances in the field of cybersecurity.